Recent trends in historical studies festchrift to professor Ravula Soma Reddy - Satyanarayana . A; Chenna Reddy . P (New Delhi : Research India Press, 2015)
"Recent Trends in Historical Studies" by A. Satyanarayana, a festschrift dedicated to Professor Ravula Soma Reddy, offers a comprehensive overview of the dynamic shifts and advancements within the field of historical research. The work meticulously examines evolving methodologies, including the integration of digital tools and interdisciplinary approaches, alongside the rise of new thematic focuses such as environmental, gender, and postcolonial studies, which are reshaping historical narratives. Satyanarayana delves into the theoretical developments that are influencing historiography and practical applications, addressing contemporary challenges like digital preservation and speculating on future trends, ultimately providing a valuable resource for scholars and students seeking to understand the contemporary landscape of historical scholarship and its adaptation to the 21st century.
Includes index.
Keywords: Historiography : modern trends; Historical research : methodology; Interdisciplinary history; Thematic developments in history; Digital history and historical preservation